From War Films to Films on War: Gendered Scenarios of National Identity—The Case of The Last Metro - Leah D. Hewitt (Studies in 20th & 21st Century Literature, 2002)
If France's ongoing struggle for self-definition in the late twentieth century involved new conceptions of citizenship and nationality, in short what it means to be French, this struggle also entailed the search for an accurate portrayal of a past in which France could recognize itself...
Keywords: French film; cinema; war films; films on war; gendered scenarios; national identity; Last Metro; self-definition; identity; female; female characters; feminism; female icon